Genome sequencing of adapted diploid potato clones - Achakkagari, Sai Reddy; Kyriakidou, Maria; Gardner, Kyle M.; De Koeyer, David; De Jong, Hielke; Strömvik, Martina V.; Tai, Helen H. (Frontiers in Plant Science, 2022)
Cultivated potato is a vegetatively-propagated crop, and most varieties are autotetraploid with high levels of heterozygosity. Reducing the ploidy and breeding potato at the diploid level can increase efficiency for genetic improvement including greater ease of introgression of diploid wild relatives and more efficient use of genomics and markers in selection. More recently, selfing of diploids for generation of inbred lines for F1 hybrid breeding has had a lot of attention in potato. The current study provides genomics resources for nine legacy non-inbred adapted diploid potato clones developed at Agriculture and Agri-Food Canada. De novo genome sequence assembly using 10x Genomics and Illumina sequencing technologies show the genome sizes ranged from 712 Mbp to 948 Mbp. Structural variation was identified by comparison to two references, the potato DMv6.1 genome and the phased RHv3 genome, and a k-mer based analysis of sequence reads showed the genome heterozygosity range of 1 to 9.04 % between clones. A genome-wide approach was taken to scan 5 Mb bins to visualize patterns of heterozygous deleterious alleles. These were found dispersed throughout the genome including regions overlapping segregation distortions. Novel variants of the StCDF1 gene conferring earliness of tuberization were found among these clones, which all produce tubers under long days. The genomes will be useful tools for genome design for potato breeding.